2017
DOI: 10.1002/pola.28751
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic chain transfer polymerization of isobutylene: The role of nucleophilic impurities

Abstract: Fast polymerization of isobutylene (IB) initiated by tert‐butyl chloride using ethylaluminum dichloride·bis(2‐chloroethyl) ether complex (T. Rajasekhar, J. Emert, R. Faust, Polym. Chem. 2017, 8, 2852) was drastically slowed down in the presence of impurities, such as propionic acid, acetone, methanol, and acetonitrile. The effect of impurities on the polymerization rate was neutralized by using two different approaches. First, addition of a small amount of iron trichloride (FeCl3) scavenged the impurity and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…We recently studied the role of various organic nucleophilic impurities such as propionic acid, acetone, methanol, and acetonitrile in CCTP. Interestingly, it was found that exo-olefin content slightly increased in the presence of ppm levels of methanol while molecular weights remained virtually identical to that obtained in the absence of methanol with [CEE]:[EADC] = 1 . There are few reports about controlled cationic polymerization for HRPIB synthesis in the presence of alcohols, and the reason for the exo content increase is still unclear.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…We recently studied the role of various organic nucleophilic impurities such as propionic acid, acetone, methanol, and acetonitrile in CCTP. Interestingly, it was found that exo-olefin content slightly increased in the presence of ppm levels of methanol while molecular weights remained virtually identical to that obtained in the absence of methanol with [CEE]:[EADC] = 1 . There are few reports about controlled cationic polymerization for HRPIB synthesis in the presence of alcohols, and the reason for the exo content increase is still unclear.…”
Section: Introductionmentioning
confidence: 95%
“…There are few reports about controlled cationic polymerization for HRPIB synthesis in the presence of alcohols, and the reason for the exo content increase is still unclear. Moreover, relatively strong nucleophiles inactivate the polymerization or decrease the concentration of active species. , In this report, we present a detailed investigation on the mechanistic role of alcohol in EADC·CEE catalyzed chain transfer polymerization of IB as well as discuss the effectiveness of tertiary alcohols compared to secondary and primary alcohols (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] Another interesting feature of t BuCl/EtAlCl 2 ÂCEE initiating system in the synthesis of HR PIB is the significant retardation of the reaction in the presence of nucleophilic impurities such as acetone, methanol, propionic acid or acetonitrile. [38] It was shown that interaction of protons with these impurities results in delay of proton transfer to monomer in the chain transfer to monomer step (see Scheme 5) leading to observed retardation of the polymerization. The negative effect of the nucleophilic impurities could be neutralized either by the addition of FeCl 3 or H 2 O (using wet hexane as reaction medium).…”
Section: H 2 O/ralcl 2 / I Pr 2 O Initiating Systemmentioning
confidence: 99%
“…The negative effect of the nucleophilic impurities could be neutralized either by the addition of FeCl 3 or H 2 O (using wet hexane as reaction medium). [38] It should be also noted that t BuCl/EtAlCl 2 ÂCEE initiating system, similarly to H 2 O/ i BuAlCl 2 /O i Pr 2 system, [33] could be used for the synthesis of HR PIB from C 4 mixed olefin feed. [39] In addition, this initiating system also displayed improved efficiency toward synthesis of HR PIB under micromixing conditions.…”
Section: H 2 O/ralcl 2 / I Pr 2 O Initiating Systemmentioning
confidence: 99%